Interpersonal relationships between the nurses and the doctors and their professional performance and quality of patient care - Kim, Esther Young Hee
This is a study of interpersonal relationships between the nurses and the doctors, professional performance, quality of patient care and linkages among these 3 concepts. To explore in a more systematic manner, relationships among these 3 concepts 2 questions were posed: 1) Are the interpersonal relationships between the nurses and the doctors directly related to the quality of patient care? 2) Are the professional performance of the nurses of the doctors directly related to the quality of patient care? The hypotheses of the study are: 1. The interpersonal relationships between the nurses and the doctors are directly related to the quality of patient care. 2. The professional performance of the nurses and the professional performance of doctors are directly related to the quality of patient care. The data were collected from December 19, 1988 to January 6, 1989 from the responses to the questionnaire by a sample of 100 nurses and 100 doctors. Statistical analysis utilized univariate analysis and bivariate analysis. Univariate analysis was used to determine the level of perceptions of the respondents on the dependent variable and independent variables. The procedures were frequency distributions, percentage, means and standard deviations. Bivariate analysis was used to determine whether there are significant relationships between the independent variables and the dependent variable. The statistical procedures used were the Pearson product moment correlation coefficient, and the F-statistics to determine the significance level of the correlation coefficient which was set at .05 for rejecting the null hypotheses. The subjects of the study were the 2nd year, 3rd year, 4th year, and chief resident physicians and the nurses who were working in the departments of medicine, surgery, pediatrics and OB and Gynecology charity wards in Philippine General Hospital. Summary of Findings and Conclusions are: 1. The perception of nurses and doctors on the quality of patient care. 2. Relationship between the dependent variable and independent variables. From the results of the study, the importance of sound interpersonal relationships between nurses and physicians as well as their professional performance in improving the quality of patient care became apparent. Based on the findings of the study, the recommendations are offered for the nurses and doctors, and the top hospital administrators (nursing, medicine, hospital).